Holocene temperature history of northwest Greenland - With new ice cap constraints and chironomid assemblages from Deltaso - Axford, Y.; Lasher, G. E.; Kelly, M. A.; Osterberg, E. C.; Landis, J.; Schellinger, G. C.; Pfeiffer, A.; Thompson, E.; Francis, D. R. (QUATERNARY SCIENCE REVIEWS, 2019)
Arctic temperature shifts drive changes in carbon cycling, sea ice extent and Greenland Ice Sheet mass balance, all of which have global ramifications. Paleoclimate data from past warm periods provide a unique means for assessing the sensitivity of these systems to warming climate, but the magnitude and timing of past temperature changes in many parts of the Arctic are poorly known. Here we assess orbital scale Holocene temperature change in northwest Greenland near the margin of the ice sheet using subfossil insect assemblages from lake Deltaso. Based upon sedimentation history in this currently proglacial lake, we also place constraints on Holocene extents of the adjacent North Ice Cap, a large independent ice cap. Reconstructed summer temperatures were warmer than present at the onset of lacustrine sedimentation following regional deglaciation by the Greenland Ice Sheet, sometime between 10.8 and 10.1 ka BP. Deltaso experienced the warmest summer temperatures of the Holocene between similar to 10 and 6.2 ka BP, followed by progressive cooling that continued through the late Holocene as summer insolation declined, culminating in the lowest temperatures during the pre-industrial last millennium. Deltaso chironomids indicate peak early Holocene summer temperatures at least 2.5-3 degrees C warmer than modern and at least 3.5-4 degrees C warmer than the pre-industrial last millennium. We infer based upon lake sediment organic and biogenic content that in response to declining temperatures, North Ice Cap reached its present-day size similar to 1850 AD, having been smaller than present through most of the preceding Holocene. Our synthesis of paleoclimate evidence from northwest Greenland, Ellesmere Island and northern Baffin Bay supports the timing of temperature trends inferred at Deltaso, and suggests that quantitative temperature reconstructions from Deltas(?) may represent a minimum bound on regional early Holocene warming. Collectively, records from the region indicate >4 degrees C summer cooling through the Holocene. Intense early Holocene warmth around northwest Greenland argues against delayed onset of warmer than -present conditions due to the influence of the nearby waning Laurentide Ice Sheet, and has implications for understanding the Greenland Ice Sheet's sensitivity to climate change. (C) 2019 Elsevier Ltd. All rights reserved.